MAKNA “PENCEMARAN LINGKUNGAN” BAGI PARA PENAMBANG EMAS TRADISIONAL: Studi fenomenologi pada para penambang emas tradisional mengenai makna pencemaran lingkungan di wilayah penambangan emas tradisional Kabupaten Tasikmalaya - Yunus Winoto (Prodi Ilmu Komunikasi Universitas Putera Batam, 2018)
Illegal gold mining activities currently increasingly prevalent in some areas in Indonesia. One of them happened in the south of West Java province precisely in Tasikmalaya Regency. There are three locations that become a place of illegal gold mining in the region that is in District Cineam, District Karangjaya and District Salopa. The existence of this illegal gold mining activity has been detrimental to many parties in addition to the mining method which is done without using safety equipment, this activity has also damaged the surrounding environment and has caused pollution due to the processing using harmful materials such as mercury (Hg), cyanide and borax. Nevertheless, some traditional gold miners consider the activities they do not incur pollution. Therefore we are interested to study the meaning of